PHILOSOPHICAL ASPECTS OF METAMODERNISM - I. Shcherov, Vladimir (Revista Gênero e Interdisciplinaridade, 2021)
The beginning of the 21st century was marked by qualitative changes in the world culture and social life, causing the need for new perceptual and conceptual models of cognition to explain them. The paradigm of postmodernism, formed in the philosophy of the 20th century, had previously determined the textual model of culture with the respective semiotic, cognitive, and anthropological criteria. However, the rapid development of the industrial civilization in the early 21st century is defining new requirements for discursive and communicative practices. Metamodernism is one of such new conceptual approaches to cultural phenomena. The authors of the article analyse the works of its main representatives, which have been actively published since 2010, and identify the key elements of the philosophical framework of metamodernism: 1) a strategy for text reconstruction; 2) a representational practice of the "structure of feeling"; 3) an aesthetic precept of "metaxis". It is difficult to formulate a comprehensive concept of metamodernism based on the analysed works due to their popular presentation style; however, if defined as a critical addition to the well-known paradigms of modernism and postmodernism, metamodernism can be perceived as an alternative worldview model that has emerged in the early 21st century with its own discursive and cognitive structure, aesthetic actualization and rational explication.